2014
DOI: 10.3109/10717544.2014.887158
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle-assisted microparticle delivery by gene guns: experiments and modeling on the effects of particle characteristics

Abstract: Microneedles (MNs) have been shown to enhance the penetration depths of microparticles delivered by gene gun. This study aims to investigate the penetration of model microparticle materials, namely, tungsten (51 mm diameter) and stainless steel (18 and 30 mm diameters) into a skin mimicking agarose gel to determine the effects of particle characteristics (mainly particle size). A number of experiments have been processed to analyze the passage percentage and the penetration depth of these microparticles in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Moreover, there are many reports on the delivery of large molecules using microneedles patch. In addressing this issue, microneedle delivery was used to enhance permeation flux of lidocaine hydrochloride and the penetration depths of microparticles delivered by gene gun (Nayak et al, 2014b;Zhang et al, 2013Zhang et al, , 2014. Moreover, optimized ultrasound combined with microneedles to further increase the permeation rates was proposed (Han & Das, 2013;Nayak et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are many reports on the delivery of large molecules using microneedles patch. In addressing this issue, microneedle delivery was used to enhance permeation flux of lidocaine hydrochloride and the penetration depths of microparticles delivered by gene gun (Nayak et al, 2014b;Zhang et al, 2013Zhang et al, , 2014. Moreover, optimized ultrasound combined with microneedles to further increase the permeation rates was proposed (Han & Das, 2013;Nayak et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…[117] The MNs can create holes in the skin and allow microparticles to penetrate deep skin even at three bar. [118] Additionally, it is demonstrated that the combination of MN pretreatment and iontophoresis could improve the skin permeation of methotrexate, particularly in defatted skin. [119] Moreover, Li et al [120] fabricated an iontophoresis-driven porous MN array patch (IDPMAP) for the delivery of charged macromolecular drugs and the IDPMAP showed ≈99% skin penetration rate, which is considerably more efficient than a pristine MN array or iontophoresis.…”
Section: In Combination With Other Devicesmentioning
confidence: 99%
“…After deciding on the proper physics and defining all of the parameters, the model should be simulated using computational software with suitable computer hardware configurations. Commonly used computational software include the updated versions of MATLAB and also COMSOL Multiphysics [ 79 , 80 ].…”
Section: Mathematical Modelling—polymeric-based Microneedlesmentioning
confidence: 99%